Globalizing central Asian human resources and soft power of Japanese education - V. Kim; N. Yem (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2022)
This paper explores the impact of globalization on the career development of students from Central Asian countries who choose Japanese studies majors and the position of Japan in the process of their career decision-making. We examine the choices and possibilities of human resource development and higher education exchange in the two regions. In particular, (1) the image of Japan among students in Central Asian countries, (2) the reasons Central Asian students choose to acquire Japanese studies majors, and (3) the impact of studying in Japan on their careers. We will analyze these points from Japan's soft power perspective.